Fundamentos para uma análise musical fenomenológica - Ricardo Miranda Nachmanowicz (2007)
This work dedicates to establish the beddings for a Phenomenological procedure of musical analysis in accordance with Edmund Husserls Phenomenology, in special of its philosophy express in the Logical Investigations and in the On the Phenomenology of the Consciousness of Internal Time, not abdicating of the processes of Phenomenologicalreduction, as of its too much workmanships. In intention to search the beddings of one future Phenomenological musical analysis, based in purely intentional processes, this work concludes with the establishment of three distinct intentional moments: 1-The musical-intention. 2-The musical-experience. 3-The musical-meaning. All these conceptsnominate intentional acts that I consider to be most elementary, each one if sending, for analytical reasons, to a distinct field of action, without excluding the proximity existing between the three, but making possible dedicated studies to one or another aspect. In a second degree there is the discussion about the importance of a rigorously phenomelogical basis, using as reference the Prolegomena to Pure Logic and Philosophy as Rigorous Science, both written by E.Husserl, as well an introduction to the philosophicsubject of phenomenology.